Strict and Comprehensive Tobacco Control Policy is Needed: A Qualitative Study Exploring How People Responding a New Policy of Pictorial Health Warning on Cigarette Package in Indonesia - Dewi, Fatwa Sari Tetra; Kusumaningrum, Fitrina; Friday, Lastdes; Baiquni, Fahmi; Urrahman, Dhiya; Kurniawan, Rama Nur; Widyatama, Rendra (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Little is known about the process on how smoker and nonsmoker responses to a Pictorial Health Warning (PHW) which is important for policy improvement. AIM: We aim to explore the nature of the reaction and the extent of impact of the PHW implementation on smoking habit in Indonesia. METHODS: We collected the data among adult aged 18+ years in Sleman District, Yogyakarta, Indonesia, involving 45 informants in in-depth interviews and 22 informants in four Focus Group Discussions, selected using the maximum variation sampling according to smoking status and area of residence. We discussed with respondents about the meaning of the PHWs, how they felt when seeing the PHWs, how those feelings emerged when seeing the PHWs, and the impact of seeing the PHWs. We analyzed the data using the content analysis. RESULTS: PHWs raised the intended negative emotional response, that wearing out over time. However, for smokers, the disease threat in the message was less obvious than to defeat smoking addiction. Smokers tried to manage their risk of illness themselves. Among non-smokers, they were more confident in being non-smokers. Both smokers and non-smokers thought that Government is half-hearted in controlling the smoking problem. Smokers were grateful, but non-smokers were sorry for this. CONCLUSIONS: The application of PHW threatens smokers but does not make them quit smoking because of the fear of defeating cigarette dependence. For non-smokers, they feel more confident to be a smoker-free. Respondents claim the government is not serious about controlling smoking.